SELF CARE: NOT JUST A TREND, BUT A NECESSITY FOR MENTAL HEALTH - Putri, Aan Iminullah Eka (International Journal of Multidisciplinary Reseach, 2025)
This article explores how self-care is not just a trend, but a necessity for mental health. Technological developments in the era of globalization, particularly through social media, have influenced public perspectives on mental health. While self-care is perceived as merely a lifestyle trend, it is essentially a basic need for maintaining optimal mental health. Mental health plays a crucial role in individual well-being, especially amidst social pressures, multiple demands, and workloads. If not managed properly, it can lead to serious mental disorders. The World Health Organization (WHO) states that mental health has equal standing with physical health in the concept of overall well-being. This study aims to understand the relationship between self-care and mental health and identify the stigma associated with mental health issues. This study used a qualitative approach with a literature review method, analyzing various academic sources, journals, and articles related to self-care, mental health, and the challenges of implementing them. The results indicate that consistent self-care practices can help individuals recognize bodily and mental signals and build healthy social relationships. Support from family and the surrounding community, mental health literacy, and stigma reduction are key factors in the successful implementation process. This research recommends strengthening education and policies that prioritize self-care as part of efforts to create a mentally healthy, productive, and prosperous society.